Adoption of self service banking channels - the case of mobile banking in India. (2017) - Kalaiarasi, H.; Lakshmi, P.; Stephan, A.
Mobile banking is an innovative, technology-based, cost efficient, expedient and time saving, self-service channel for banking customers as compared to conventional branch banking. Though India has a strong potential for mobile banking usage, it is observed that only 5% of mobile subscribers are registered users of mobile banking, which is very low as compared to other developed countries. This study explores the aspects that affect an individual's intention to adopt mobile banking services in India. Perceived risk is a critical factor that can influence adopting or continuing with any new technology. Hence, a modified model of Brown et al. (2003) that merges risk perception with the features proposed by decomposed theory of planned behaviour, diffusion of innovation theory is developed and tested in the Indian context. The results reveal that adoption of mobile banking by Indian customers is affected by lack of security and privacy, whereas innovation features such as relative advantage, compatibility, trialability, self-efficacy and technology support positively influence mobile banking adoption.